Analytically continued fock space multi-reference coupled-cluster theory: application to the shape resonance - Pal, Sourav; Sajeev, Y.; Vaval, Nayana (Chemical Physics, 2006)
The Fock space multi-reference coupled-cluster (FSMRCC) method is used for the study of the shape resonance energy and width in an electron-atom/molecule collision. The procedure is based upon combining a complex absorbing potential (CAP) with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigen-value problem. We study the shape resonances in e(-)-C2H4 and e(-)-Mg. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: complex absorbing potential; correlated independent particle potential; Fock space multi-reference coupled-cluster theory; shape resonance

Shape resonance in electron molecule scattering using coupled cluster method - Pal, Sourav; Vaval, Nayana; Sajeev, Y. (Indian Journal of Physics and Proceedings of the Indian Association for the Cultivation of Science, 2007)
The Fock space multi-reference coupled-cluster (FSMRCC) method along with the complex absorbing potential (CAP) is used for the study of the shape resonance energy and width in an electron molecule collision. We study the shape resonances in e(-) -H2CO and e(-) -CO.
Keywords: electron-molecule scattering; multi-reference coupled-cluster

Coupled cluster methods for autoionisation resonances - Sajeev, Y.; Ghosh, A.; Vaval, N.; Pal, S. (International Reviews in Physical Chemistry, 2014)
The quantum chemical calculation of autoionisation resonances in many-electron systems is a highly challenging task due to the ionisation continuum involved. Recently, advances were reported where conventionally used ab initio codes can be employed to compute autoionisation resonances. This is made possible by the use of analytical continuation tools such as complex scaling and complex absorbing potential (CAP) in the electronic structure codes. We review the formulation and the use of complex scaling and CAP in coupled cluster methods for the electron correlated calculation of energy position and autoionisation decay rate of resonance states. The application of analytically continued coupled cluster method for the correlated calculation of interatomic or intermolecular Coulombic decay process is also discussed.
Keywords: autoionisation resonances; complex absorbing potential; complex scaling; equation-of-motion coupled cluster; Fock space multi-reference-coupled cluster; intermolecular Coulombic decay

Negative ion resonance states: the fock-space coupled-cluster way - Basumallick, Suhita; Sajeev, Y.; Pal, Sourav; Vaval, Nayana (Journal of Physical Chemistry A, 2020)
The negative ion resonance states, which are electron-molecule metastable compound states, play the most important role in free-electron controlled molecular reactions and low-energy free-electron-induced DNA damage. Their electronic structure is often only poorly described but crucial to an understanding of their reaction dynamics. One of the most important challenges to current electronic structure theory is the computation of negative ion resonance states. As a major step forward, coupled-cluster theories, which are well-known for their ability to produce the best approximate bound state electronic eigen solutions, are upgraded to offer the most accurate and effective approximations for negative ion resonance states. The existing Fock-space coupled-cluster (FSCC) and the equation-of-motion coupled-cluster (EOM-CC) approaches that compute bound states are redesigned for the direct and simultaneous determination of both the kinetic energy of the free electron at which the electron-molecule compound states are resonantly formed and the corresponding autodetachment decay rate of the electron from the metastable compound state. This Feature Article reviews the computation of negative ion resonances using the FSCC approach and, in passing, provides the highlights of the equivalent EOM-CC approach.